Cardiovascular Disease and All-Cause Mortality in Male Twins With Discordant Cardiorespiratory Fitness: A Nationwide Cohort Study. Issue 10 (14th April 2020) - Ballin, Marcel; Nordström, Anna; Nordström, Peter
Abstract: Whether genetic and familial factors influence the association between cardiorespiratory fitness (CRF) and cardiovascular disease (CVD) is unknown. Two cohorts were formed based on data from 1, 212, 295 men aged 18 years who were conscripted for military service in Sweden during 1972–1996. The first comprised 4, 260 twin pairs in which the twins in each pair had different CRF (≥1 watt). The second comprised 90, 331 nonsibling pairs with different CRF and matched on birth year and year of conscription. Incident CVD and all-cause mortality were identified using national registers. During follow-up (median 32 years), there was no difference in CVD and mortality between fitter twins and less fit twins (246 vs. 251 events; hazard ratio (HR) = 1.00, 95% confidence interval (CI): 0.83, 1.20). The risks were similar in twin pairs with ≥60-watt difference in CRF (HR = 0.96, 95% CI: 0.57, 1.64). In contrast, in the nonsibling cohort, fitter men had a lower risk of the outcomes than less fit men (4, 444 vs. 5, 298 events; HR = 0.83, 95% CI: 0.79, 0.86). The association was stronger in pairs with ≥60-watt difference in CRF (HR = 0.65, 95% CI: 0.59, 0.71). These findings indicate that genetic and familial factors influence the association of CRF with CVD and mortality.